Acceptability of malaria rapid diagnostic tests administered by village health workers in Pangani District, North eastern Tanzania. (December 2016) - Mushi, Adiel; Massaga, Julius; Mandara, Celine; Mubyazi, Godfrey; Francis, Filbert; Kamugisha, Mathias; Urassa, Jenesta; Lemnge, Martha; Mgohamwende, Fidelis; Mkude, Sigbert; Schellenberg, Joanna
Abstract Background Malaria continues to top the list of the ten most threatening diseases to child survival in Tanzania. The country has a functional policy for appropriate case management of malaria with rapid diagnostic tests (RDTs) from hospital level all the way to dispensaries, which are the first points of healthcare services in the national referral system. However, access to these health services in Tanzania is limited, especially in rural areas. Formalization of trained village health workers (VHWs) can strengthen and extend the scope of public health services, including diagnosis and management of uncomplicated malaria in resource-constrained settings. Despite long experience with VHWs in various health interventions, Tanzania has not yet formalized its involvement in malaria case management. This study presents evidence on acceptability of RDTs used by VHWs in rural northeastern Tanzania. Methods A cross-sectional study using quantitative and qualitative approaches was conducted between March and May 2012 in Pangani district, northeastern Tanzania, on community perceptions, practices and acceptance of RDTs used by VHWs. Results Among 346 caregivers of children under 5 years old, no evidence was found of differences in awareness of HIV rapid diagnostic tests and RDTs (54 vs. 46 %, p = 0.134). Of all respondents, 92 % expressed trust in RDT results, 96 % reported readiness to accept RDTs by VHWs, while 92 % expressed willingness to contribute towards the cost of RDTs used by VHWs. Qualitative results matched positive perceptions, attitudes and acceptance of mothers towards the use of RDTs by VHWs reported in the household surveys. Appropriate training, reliable supplies, affordability and close supervision emerged as important recommendations for implementation of RDTs by VHWs. Conclusion RDTs implemented by VHWs are acceptable to rural communities in northeastern Tanzania. While families are willing to contribute towards costs of sustaining these services, policy decisions for scaling-up will need to consider the available and innovative lessons for successful universally accessible and acceptable services in keeping with national health policy and sustainable development goals.